Advances in nanotechnology in drug delivery systems for burn wound healing: a review - Khan, Abida; Mostafa, Howayada Mahany; Almohammed, Khalid Hassan; Singla, Neelam; Bhatti, Zohra; Siddique, Muhammad Irfan (Oriental Scientific Publishing Company, 2025)
Burn wounds (BWs) are among the most complex injuries to manage, often leading to prolonged healing times, heightened infection risks, and significant scarring. Traditional therapies frequently fall short in addressing these challenges, highlighting the need for innovative solutions. Nanotechnology has emerged as a transformative approach in BWs care, offering advanced drug delivery systems that improve therapeutic outcomes. These systems, including nanoparticles, liposomes, micelles, and hydrogels, provide controlled drug release, enhanced stability, and targeted delivery of bioactive compounds. This review explores recent advancements in nanotechnology-based drug delivery for BWs, emphasizing their potential to promote faster healing, reduce infections, and minimize scarring. Additionally, emerging technologies, such as stimuli-responsive nanomaterials and theranostic platforms, hold promise for personalized treatment approaches. By integrating these innovations, nanotechnology is paving the way for more effective, patient-centered BWs management strategies